Application of Caseinate Modified with Maillard Reaction for Improving Physicochemical Properties of High Load Flaxseed Oil Microcapsules. Issue 5 (26th February 2021) - Zhang, Wenbin; Chen, Zhengjun; Yang, Ruijin; Hua, Xiao; Zhao, Wei; Guan, Shuyi
Abstract: High‐load flaxseed oil microcapsule is prepared with the Maillard reaction products (MRPs) of sodium caseinate and isomaltooligosaccharide as wall material. It is found that the emulsifying activity index and emulsion stability index of MRPs are increased by 31.32% and 34.11% respectively at the appropriate degree of graft (26.30%) compared with the mixture of sodium caseinate and isomaltooligosaccharide. Smaller droplet size and lower polydispersity index can be achieved in the flaxseed oil emulsions coated by MRPs, due to the change of sodium caseinate molecular weight and spatial structure. The microencapsulation efficiency of the microcapsules coated by MRPs is highly improved up to 98.22% at oil load of 58.43%, compared with the control group. Furthermore, MRPs as coating material can protect flaxseed oil against lipid oxidation at 50 °C for 4 weeks. More importantly, the smooth, round, and compact external surface structures of microcapsule powder support its physical necessity for industrial usage. Due to its high microencapsulation efficiency and good oxidation stability, MRPs formed with sodium caseinate and isomaltooligosaccharide show great application potential in preparing high load oil microcapsule. Practical Applications : Findings in this research could be utilized for developing microencapsulation loaded with higher concentration of flaxseed oil, a rich source of α‐linoleic acid and lignans. Application of MRPs (Maillard reaction products) formed through interaction between sodium caseinate and isomaltooligosaccharide by heating improved both its physicochemical properties and oxidative stability. It is a novel approach for developing microcapsule with higher percentages of oils with better oxidative stability. Abstract : Maillard reaction products (MRPs) of sodium caseinate and isomaltooligosaccharide can bring out wall material suitable for microencapsulation of flaxseed oil. Due to the increased emulsifying activity index and emulsion stability index of MRPs, smaller droplet size and lower polydispersity index are achieved. The microencapsulation efficiency of the microcapsules coated by MRPs is highly improved up to 98.22% at oil load of 58.43%. When stored at 50 °C for 4 weeks, lipid oxidation are well lowered. Meanwhile, the smooth, round, and compact external surface structures of microcapsule powder support its physical necessity for industrial usage.